Product Variety Under Brand Influence: An Empirical Investigation of Personal Computer Demand - Hui, Kai-Lung (Management Science, 2004)
Prior research suggests that brand may influence consumer preference for differentiated products. However, the extant literature does not measure how brand value affects product similarity and consumer choice. This paper examines demand response to the proliferation of personal computers (PCs). Using both the central processing unit (CPU) and brand as segmentation variables, I construct a two-level nested generalized extreme value (GEV) discrete choice model to estimate the brand values and product similarities of a set of PC vendors. With these estimates, I infer the relative efficacy of product variety for firms which possess different degrees of brand values. My results suggest that consumers treat PCs from the same firm as close substitutes, and the proximity of the PCs correlates positively with the firms’ brand values. This finding suggests that there are decreasing demand returns to product variety for branded multiproduct firms. I discuss a few possible drivers of brand value and explore the significance of product line extension in building long-term brand reputation.